On the behavior of the n1(K, T)A n2 series of doubly excited states in He-like atoms immersed in weakly coupled plasmas (2014)
ABSTRACT: The stability of resonant states in Helium-like atoms while under the influence of a plasma environment is studied. We analyze the variation of resonance parameters (energies and lifetimes) against the strength of the screening parameter within the Debye-H¨uckel model. We use a Feshbach-like projection formalism with explicitly correlated CI-wave functions to uncover the evolution of resonance parameters until they cross the upper Aq+ (N=2) threshold, and a complex scaling method to analyze the survival of these Feshbach resonances across the threshold, which eventually makes them behave as shape resonances.